(untitled) (Biological Sciences - PJSIR, 2001)
The 1, 3-diphenylpyrazole-4-carboxaldehyde benzoyl hydrazone on reaction with various metals gave corresponding complexes which were characterized through their metal analysis and by applying spectrophotometeric techniques. Stability constants of these complexes were also calculated by spectrophotometric Job’s continuous variation method. A tentative structure of complexes involving co-ordination through nitrogen and oxygen of the hydrazone moiety with the metals is suggested.